DESIGN OF PHYSICAL PRACTICUM TOOLS ON ROTATIONAL DYNAMICS MATTER WITH SCIENTIFIC CONCEPT - Fretty Doharni Ritonga; Betty M Turnip (Jurnal Pendidikan Fisika, 2018)
This study aims to produce sufficient practicum tools on the matter of dynamics of rotation with scientific concepts, to know the activities of students in learning when using the tool of the design result, to know the improvement of students' cognitive learning outcomes if in learning using the tool of the design result. This type of research belongs to Research and Development (R & D). The population of this research is the entire class XI semester 1 academic year 2017/2018 in SMA Negeri 2 Binjai. The sample specified in this study is one of the class XI of all classes in the research site that is class XI MIA 3. The procedure in the research is the stage of needs analysis, design phase, development and implementation stage. The research instrument uses a review questionnaire or response from a media expert, an assessment questionnaire or a response from a physics teacher, an assessment questionnaire or a student's response to the design of the practicum tool and the Observation. The conclusions obtained from the research are developed practicum tools get positive response from students, the activities undertaken by students during learning is quite active and experienced increase in each meeting, student learning outcomes increased significantly